SISTEM INFORMASI RESERVASI KAMAR HOTEL BINTANG TIMUR BERBASIS WEB - Adriana, Windy; -, Elzas; Amirin, M. Ikram; Windy Adriana (FORTECH (Journal of Information Technology), 2024)
The Hotel Room Reservation management system is able to provide convenience in the daily reservation service process, which is capable of displaying and processing the information required from a hotel's activities, including the number and position of visitors, income, available booking rooms, booking list, etc. The design of this system is expected to make it easier for East Jambi hotels to process data related to hotel room reservation management. The aim of this Thesis for the Room Reservation Information System at the Bintang Timur Hotel Jambi is to facilitate the processing of hotel room reservation data at the Bintang Timur Hotel Jambi. The main elements in forming a system consist of input, process, and output. The input required for this system is input of employee data, guest data, service data, room data and room reservation data. With a process that includes employee data processing, guest data processing, service data processing, room data processing and room reservation data processing, which will produce an output report on hotel room reservation transactions. The software development uses Visual Studio Code as a text editor, a web-based interface is built using the HTML, PHP, CSS programming languages to facilitate the application development process with the PhpMyAdmin database. From this research, a design for the Bintang Timur Jambi Hotel Room Reservation Information System was produced which can simplify the processing of hotel room reservation data and the preparation of reports.